Measuring perceived service quality using SERVQUAL - Marković, Suzana (Management, 2010)
The purpose of the study is to examine customers'' perceptions of service quality in the Croatian hotel industry. The aim is to assess the perceived service quality of hotel attributes and to determine the factor structure of service quality perception. A modified servqual scale was used to assess service quality perceptions from the perspective of domestic and international tourists. Data were collected in 15 hotels in the Opatija Riviera (Croatia), using a self-administered questionnaire. Descriptive statistical analysis, exploratory factor analysis and reliability analysis were conducted. The study results indicate the rather high expectations of hotel guests regarding service quality. ''Reliability'', ''empathy and competence of staff'', ''accessibility'' and ''tangibles'' are the key factors that best explained customers'' expectations of hotel service quality. The results of the quantitative assessment of perceived service quality may provide some insights on how customers rate the service quality of a particular hotel. Thus, the findings can be used as a guide for hotel managers to improve the crucial quality attributes and enhance service quality and business performance.
Keywords: Croatia; Hrvaška; hotelirstvo; hoteli; storitve; kvaliteta; merjenje; anketiranje